1996
DOI: 10.1021/ic9601706
|View full text |Cite
|
Sign up to set email alerts
|

Four- and Five-Coordinate Oxovanadium(V) Alkoxides:  Do Steric Effects or Electronic Properties Dictate the Geometry?

Abstract: Sterically hindered ligands generally form metal complexes with lower coordination numbers than less hindered ligands. In contrast to dogma, the solid state vanadium(V) complexes with ethylene glycol and pinacol contain four- and five-coordinate vanadium atoms, respectively. Ab initio and electrostatic potential distribution calculations were conducted on both experimental and optimized geometries of the four- and five-coordinate oxovanadium chloroalkoxides. Ab initio energy calculations favor the five-coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Spectroscopic, 307,382,383 theoretical, 96,384 and solid-state model studies 87,355,363,364,376,377 were key in confirming that the vanadium atom was fivecoordinate. 307,383 Although this ruled out suggestions of four-and six-coordinate derivatives, three fivecoordinate structures remained.…”
Section: Characterization Of the Nucleoside-vanadate Complexes That Fmentioning
confidence: 93%
See 1 more Smart Citation
“…Spectroscopic, 307,382,383 theoretical, 96,384 and solid-state model studies 87,355,363,364,376,377 were key in confirming that the vanadium atom was fivecoordinate. 307,383 Although this ruled out suggestions of four-and six-coordinate derivatives, three fivecoordinate structures remained.…”
Section: Characterization Of the Nucleoside-vanadate Complexes That Fmentioning
confidence: 93%
“…93 A theoretical evaluation of the effects of ligands on vanadium coordination geometry in these simple systems suggested that electronic effects did not induce the coordination differences, but that subtle ligand effects such as the gem-dimethyl effect were invoked. 96 Of the numerous complexes structurally characterized, the system with the cyclopentanol ligand resulted in the vanadium atom showing differential V-O bond lengths (up to about 0.3 Å) (16) depending on whether the alkoxide group was directly bound to the vanadium or merely associated with its dinuclear partner. 88 This structure clearly reflects the favorable alkoxide association even with cyclopentanol, a sterically bulky ligand.…”
Section: Structural Model Studies Of Vanadate Estersmentioning
confidence: 99%
“…The first structurally characterized model systems showed the tendency of vanadium(V) to form five-coordinate alkoxides [71][72][73][74][75][76]. A vanadium(V) alkoxide formed from the reaction of pinacol with VOCl 3 provided this structural precedent for the transition-state structure used in biological studies (4) [72], modeling the vanadate-ribonuclease complex [77,78].…”
Section: What Are the Structures Of Vanadium Complexes In Solution?mentioning
confidence: 99%
“…Indeed this replacement used by the Zubieta group provided the first structural example of a monomeric vanadium(V) alkoxide complex with four-coordinate vanadium [81]. A dinuclear complex from ethylenediol demonstrated that four-coordinate vanadium(V) was a very stable alternative to the five-coordinate form [76,82]. The vanadium(V) alkoxides associate in solution [83], but the high reactivity could be decreased if bulky ligands were employed, and a variety of such systems have been reported (see below for more details) [75,84].…”
Section: What Are the Structures Of Vanadium Complexes In Solution?mentioning
confidence: 99%
“…Subtle variations in the vicinity of the small V +5 ion may result in large changes in the stability and reactivity of oxovanadium(V) complexes [1,6,[20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Oximes, including internally functionallized oximes, constitute an important class of N/O type donor ligands [34][35][36][37][38][39] because of their varying coordination abilities with the metal centers.…”
Section: Introductionmentioning
confidence: 99%